(untitled) (Physical Education, Health and Social Sciences, 2025)
Color vision is the eyes capacity to distinguish between distinct light wavelengths, which allows for the experience of color. The retinas cone cells, which react too various light wavelengths to create a variety of colour experiences, help with this function. The objective of this study is to “Assessment of color vision in blood cancer patients”. This descriptive cross-sectional study includes 100 clinically diagnosed blood cancer patients between the age range of 20-40. Color vision was assessed by Ishihara plates. The study included 100 participants, with a higher proportion of males (62%) compared to females (38%). The majority of participants had leukemia for 1-12 months (79%), while 21% had leukemia for 13-24 months. Regarding right eye diagnosis, 80 participants (80%) had normal vision, 11 (11%) had protanopia, and 9 (9%) had deuteranopia. For the left eye, 72 participants (72%) had normal vision, 19 (19%) had protanopia, and 9 (9%) had deuteranopia. When analysing vision diagnosis by gender, among males, 46 had normal vision in the right eye, 9 had protanopia, and 7 had deuteranopia, while among females, 34 had normal vision, 2 had protanopia, and 2 had deuteranopia. In the left eye, 41 males had normal vision, 14 had protanopia, and 7 had deuteranopia, whereas among females, 31 had normal vision, 5 had protanopia, and 2 had deuteranopia. To investigate the relationship between leukemia duration and vision diagnosis, a chi-square test was conducted. For the right eye, the test result (χ² = 1.330, p = 0.514) showed no significant association between leukemia duration and vision impairment. Similarly, for the left eye, the chi-square test (χ² = 1.525, p = 0.466) also indicated no significant relationship. These findings suggest that the duration of leukemia does not have a statistically significant impact on vision diagnosis in either eye. No significant association was found between gender, leukemia duration, and the diagnosis categories for both the right and left eyes.